Assessing the risk of falls of older people using specialized diagnostic tests - Florczak, Aleksander; Szmelcer, Beniamin; Krakowska, Natalia; Fortuna, Aleksandra; Wszelaki, Patrycja; Zaborna, Daria; Wilczyński, Michał; Ciepłuch, Justyna; Skierkowska, Natalia; Wąsicki, Mariusz; Modrzejewski, Mateusz; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2019)
Background: The phenomenon of population aging, resulting in an increase in the number of elderly people in need of medical assistance, necessitated the development of geriatric medicine. Its key assumption is to improve the quality of life of older people through early recognition, prevention and treatment of diseases of old age.Material and methods: Analysis of available literature, articles in the Google Scholar and PubMed database using keywords: geriatrics, aging process, fallsResults: The fall belongs to a group of great geriatric problems contributing to the phenomenon of senile disability. The result of disturbances in the balance and problems associated with the weakening of the musculoskeletal system is a fall, which has very serious consequences for the health and functioning of an older person. The most important diagnostic tests related to falls of older people include: Timed Up & Go Test (TUG), Dynamic Gait Index (DGI), The Step Test, Stop Walking When Talking (SWWT), Four Square Step Test (FSST)Conclusions: Falling older people is statistically one of the biggest problems of this age group, and at the same time causing a huge number of complications in the lives of geriatric patients, which is why their prevention is so important. There is a further need for research and discussion on the effectiveness of forms of diagnostic to prevent the falls of older people